Change Management Strategies: Building Organizational Resilience in the Digital Era - Candrasa, Limega; Cahyadi, Lukieto; Cahyadi, Willy; Cen, Cia Cai (Journal of Ecohumanism, 2024)
This research project aims to analyse effective change management strategies for building organisational resilience in the digital era, with a particular focus on a case study of PT SBS, a company undergoing digital transformation. The digital era requires companies to adapt rapidly to technological changes and a dynamic business environment. Therefore, a strategic approach to change management is essential to ensure the organisation's survival and competitiveness. This research employs a qualitative methodology to gain a nuanced understanding of the experiences and perspectives of PT SBS managers and employees engaged in the transformation process. The research elucidates the methods by which they manage change, overcome challenges and capitalise on the opportunities afforded by digital technology. The results demonstrated that adaptive leadership was a significant factor in the success of change at PT SBS. Managers who are able to adapt rapidly to technological developments and modify their leadership style in accordance with organisational requirements have a beneficial impact on employees' preparedness for change. Adaptive leadership also encompasses the capacity to make prompt decisions, respond to feedback and motivate teams to innovate.